Development of Mobile-Based Illegal Cigarette Data Management Using Rapid Application Model - Adam Bachtiar Maulachela; Jian Budiarto; Ahmad Ashril Rizal; Lalu Puji Indra Kharisma (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Indonesia is one of the highest cigarette-consuming countries in the world. Therefore, the government is trying to control this through various efforts. One of them is by increasing the excise rate on tobacco products yearly with an average increase of 10.92 percent per year. However, this effort has not been able to reduce the number of smokers in Indonesia, which has increased by 8.8 million in the last ten years. This raises the fact that there is an increase in the circulation of illegal cigarettes in Indonesia. Therefore, the central and local governments formed task forces to control illegal cigarettes. This study aims to assist the task force in managing data on the circulation of illegal cigarettes by creating a data management application. This application was developed by implementing the Rapid Application Development (RAD) method. This method consists of four main stages: requirements engineering, system design, development, and implementation. This research has produced an Android-based mobile application that can assist the task force in managing illegal cigarette data. Based on the test results, this application has been declared successful through quality and functionality tests, so it is ready for use by the task force